(untitled) (Revista de Ciências Agroveterinárias, 2013)
The yield, health and quality of onion (Allium cepa L.) are influenced by plant nutrition mainly by nitrogen (N), which besides being required in large amounts, is easily leached from the soil. The experiment aimed to compare the system of fertilization and pest management to the conventional use of alternative methods on yield, thrips incidence, and conservation of onion bulbs post-harvest. For this purpose an experiment was conducted in 2010, in Cambisol, Ituporanga, SC. The treatments were conventional (mineral fertilizer and pesticides), organic fertilizer and fertigation of liquid biofertilizer (BF) the basis of turkey manure, organic fertilizer and irrigation with BF based manure EB), and organic fertilizer with spraying EB biofertilizer at 3%. The cultivar used was Epagri 352 Bola Precoce. Sowing, transplanting and harvesting were performed in 03/05, 12/07 and 06/12/2010, respectively. The conventional and organic management with biofertilizers did not reduce the damage caused by thrips, the use of biofertilizers not increased losses postharvest, the yield in the organic system (organic fertilization with biofertilizers) was reduced in 43% when compared to conventional.